2009
DOI: 10.1017/s0714980809990031
|View full text |Cite
|
Sign up to set email alerts
|

The Canadian Community Health Survey as a Potential Recruitment Vehicle for the Canadian Longitudinal Study on Aging

Abstract: The goal of the Canadian Longitudinal Study on Aging (CLSA) is to recruit 50,000 participants aged 45 to 85 years of age and follow them for at least 20 years. The sampling and recruitment processes for a study of this scope and magnitude present important challenges. Statistics Canada was approached to collaborate with the CLSA with the goal of determining whether the Canadian Community Health Survey (CCHS) could be used as a recruitment vehicle for the CLSA. In this pilot study conducted in 2004, it was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…The lower age limit at the baseline also allowed inclusion of a sample from the baby boom cohort (i.e. those born between 1946 and 1964) that will constitute a significant percentage of older adults in the coming years 9 , 10 . The upper age limit was set to keep the focus on adults who have reached old age living in the community.…”
Section: Who Is In the Cohort?mentioning
confidence: 99%
“…The lower age limit at the baseline also allowed inclusion of a sample from the baby boom cohort (i.e. those born between 1946 and 1964) that will constitute a significant percentage of older adults in the coming years 9 , 10 . The upper age limit was set to keep the focus on adults who have reached old age living in the community.…”
Section: Who Is In the Cohort?mentioning
confidence: 99%
“…The first sampling frame for the CLSA was the CCHS 14. To reach the intended sample of 20 000 participants, tracking participants were also recruited through provincial healthcare registration databases and random digit dialling.…”
Section: Methodsmentioning
confidence: 99%
“…The CCHS response rate was 66% in 2013–2014. 14 , 15 The representativeness of the cNICS sample may be one contributor to the differing coverage estimates observed between cNICS and P/Ts. Previous Canadian research has found that respondents to other immunization surveys are more likely to be UTD, as compared with non-responders.…”
Section: Resultsmentioning
confidence: 99%